Development of Facilites for Aviation Safety Services - Fairlya Anissanadhea; Surya Tri Saputra; Dhian Supardam (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Aviation is a unit that cannot stand on its own. Aviation consists of the use of airspace, aircraft, airports, air transportation, flight navigation, environmental safety and security and other facilities. The data collection carried out in this study was based on the author's observations and data on the Cakrabhuwana Cirebon Standard Operating Procedure from November 2021 to January 2022, to obtain results in carrying out their duties. Based on the author's observations, the lack of facilities at Cakrabhuwana Cirebon Airport can have consequences that can interfere with flight safety.